\(a^3+b^3+c^3-3abc=0\)
\(\Leftrightarrow\left(a+b\right)^3+c^3-3ab\left(a+b\right)-3abc=0\)
\(\Leftrightarrow\left(a+b+c\right)\left[\left(a+b\right)^2-\left(a+b\right)\cdot c+c^2\right]-3ab\left(a+b+c\right)=0\)
\(\Leftrightarrow\left(a+b+c\right)\left(a^2+b^2+c^2-ab-bc-ca\right)=0\)
Khi đó xảy ra 2 trường hợp:
TH1:\(a+b+c=0\Rightarrowđpcm\)
\(TH2:a^2+b^2+c^2-ab-bc-ca=0\)
\(\Leftrightarrow a^2+b^2+c^2=ab+bc+ca\)
Áp dụng BĐT Bunhiacopski ta có:
\(\left(1^2+1^2+1^2\right)\left(a^2+b^2+c^2\right)\ge\left(1\cdot a+1\cdot b+1\cdot c\right)^2\)
\(\Rightarrow3\left(a^2+b^2+c^2\right)\ge a^2+b^2+c^2+2\left(ab+bc+ca\right)\)
\(\Rightarrow a^2+b^2+c^2\ge ab+bc+ca\)
Dấu "=" xảy ra tại a=b=c
Vậy \(a^3+b^3+c^3=3abc\) thì \(a+b+c=0\) hoặc \(a=b=c\)